2013
DOI: 10.48550/arxiv.1303.3971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flavour physics from lattice QCD

Elvira Gámiz

Abstract: I review recent results and prospects for improvement in calculations of hadronic matrix elements relevant to quark flavour phenomenology. I will focus on key quantities for CKM unitarity triangle analyses and for the study of discrepancies between experiment and SM predictions for some flavour observables.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…which are not yet included in the FLAG average but having smaller errors are consistent with the latter Evidently there is a big progress in determining all these relevant parameters but one would like to decrease the errors further and it appears that this should be possible in the coming years. Selected reviews about the status and prospects can be found in [62,[121][122][123][124][125].…”
Section: Step 2: Improved Lattice Calculations Of Hadronic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…which are not yet included in the FLAG average but having smaller errors are consistent with the latter Evidently there is a big progress in determining all these relevant parameters but one would like to decrease the errors further and it appears that this should be possible in the coming years. Selected reviews about the status and prospects can be found in [62,[121][122][123][124][125].…”
Section: Step 2: Improved Lattice Calculations Of Hadronic Parametersmentioning
confidence: 99%
“…In order to simplify the presentation we still work with η Y and Y 0 (x t ) which should be replaced by Y eff in (123) if the future precision of experimental data will require it.…”
Section: Tree-level Gauge Boson Exchangementioning
confidence: 99%
“…For the numerics in Section 3 we however use the relation (11) without the lattice input, except for Eq. ( 29) below where we use (13).…”
Section: ∆F = 2 Observablesmentioning
confidence: 99%
“…Before entering our analysis we want to find the range for γ by using the range for ξ in Table 1 together with formulae (11) and (14). We find independently of S(v) (15) GeV [37] m Bs = 5366.8(2) MeV [38] sin 2 θ W = 0.23116 (13) [37] F B d = (188 ± 4) MeV [36] α(M Z ) = 1/127.9 [37] F Bs = (225 ± 3) MeV [36] α s (M Z ) = 0.1184 (7) [37] (11), BBs = 1.33 (6)[20] m d (2 GeV) = (4.73 ± 0.12) MeV [20] BBs / BB d = 1.05 (7) [20] (11) MeV [20] S ψK S = 0.679 (20) [37] BK = 0.767 (10) [20] S ψφ = −0.01 ± 0.08 [45] κ ǫ = 0.94 (2) [6, 34] ∆Γ s = 0.116 ± 0.019 [46] η cc = 1.87 (76) [47] τ Bs = 1.503 (10) ps [44] η tt = 0.5765 (65) [41] τ B d = 1.519( 7) ps [44] η ct = 0.496 (47) [48] τ B ± = (1641 ± 8) × 10…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation